Effects of specific hip muscle activation exercise using realt-time biofeedback on dynamic knee control in jumping performance in female athletes: Results of a pilot study - Hajduk, K.; Rebtschinski, J.; Schlumberger, A.; Schmidtbleicher, D. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Increasing evidence in the literature indicates that improved triplanar neuromuscular control of the hip and knee muscles may have a positive influence on dynamic frontal plane knee joint control and knee-joint loading, especially in female athletes (Clairborne et al., 2006). Based on this assumption the purpose of the study was to investigate the effects of a specifically arranged training program of hip and knee muscle activation exercises on dynamic control adjustments of the knee joint in the frontal plane and iumping performance in a CMJ. Methods: Participants (n 23, age 22.1 ± 1.6) were evaluated for (a) standing frontal plane knee joint angle (FPKJA, i.e. varus/valgus) in anatomical position and (b) for dynamic FPKJA during the eccentric and concentric movement phases of the CMJ, using a 2D video analysis system (Simi Aktysis, 100 fps). Changes in the amount of dynamic excursion of FPKJAs are defined by the difference between peak FPKJA during standing and peak dynamic displacement of FPKJA during both eccentric and concentric movement phases, termed peak range of motion (PROM). Two pretests were examined prior to the study to determine approximate jumping performance FPKJA. Training exercises included two types of miniband exercises and two more complex exercises guided by a visual and accoustic 2D biofeedback device (Simi Aktysis). Subjects trained for 4 weeks, 3 days per weeks. Results: Vertical jump height improved significantly by 1.1 ± 1.5 cm (3.7 ± 9.9%; p < 0.01). Post-testing data indicates that dynamic PROM of FPKJA significantly moved toward more varus displacement during the eccentric (-6.1 ± 10.4°; 6 ± 9.2%) as well as concentric phase (-5.8 ± 15.1°; 549 ± 21.6%) before take-off (p . 0.05 for both phases). Discussion: Major findings demonstrate that the training program had a positive influence on muscle power development during a stretch-shortening-cycle. Although the relative contribution of single exercises is speculative, the combination of those exercises focusing on improving intra- and inter-muscular coordination of hip and knee muscles might be responsible for an improved synergistic control mechanism within the kinetic chain of the lumbop-pelvic hip complex and the lower extremities. However, improvements in jumping performance seem to correlate negatively with an increased amount of frontal plane knee varus (PROM) during the eccentric (r -0.32) as well as in the concentric movement phase (r -0.303) when preparing for take-off in CMJ.